Effect of in-bag carcass decontamination method on shelf life of whole chicken carcasses packaged in plastic bags - Uysal, Ibrahim Alper; Incili, Gokhan Kursad; Cakmak, Omer; Calicioglu, Mehmet (Tubitak Scientific & Technological Research Council Turkey, 2020)
This study was undertaken to investigate the changes in the microbiological and sensorial attributes of fresh chicken carcasses immersed in decontamination solutions, followed by packaging in plastic bags in which decontamination solution was added during storage at 4 degrees C. The samples were taken on days 0, 3, 7, and 10 for microbiological and sensory attributes. Results showed that there was a limited antimicrobial effect on microbial flora in the treatment groups within the first 3 days of storage compared to the control group. However, the difference between the groups completely disappeared on days 7 and 10. The changes in the numbers of the microflora between days 0 and 10 varied between 4.5-7.9 log(10) CFU/mL for total aerobic mesophiles, 3.6-8.58 log(10) CFU/mL for psychrotrophic bacteria, 2.7-6.7 log(10) CFU/mL for coliforms, and 2.2-5.9 log 10 CFU/mL for yeast and molds. Sensory evaluation of the cooked breast meat of the carcasses indicated that there was no appreciable difference between the groups between days 0 and 7. It was concluded that the in-pack decontamination method described here should be improved for antimicrobial effect and has potential to be used without affecting sensory attributes of the carcasses in poultry.
Keywords: Chicken; coliform; decontamination; Salmonella spp.; shelf life